2017
DOI: 10.1038/s41598-017-15427-0
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of the inner cell mass in mouse blastocyst is restricted by the activity of FGF/MAPK pathway

Abstract: In order to ensure successful development, cells of the early mammalian embryo must differentiate to either trophectoderm (TE) or inner cell mass (ICM), followed by epiblast (EPI) or primitive endoderm (PE) specification within the ICM. Here, we deciphered the mechanism that assures the correct order of these sequential cell fate decisions. We revealed that TE-deprived ICMs derived from 32-cell blastocysts are still able to reconstruct TE during in vitro culture, confirming totipotency of ICM cells at this sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 56 publications
4
35
0
Order By: Relevance
“…Our results show that the global positional features (see Terminology Box) of NANOG and GATA6 in early blastocysts do not show a pattern. This lack of a pattern might allow for the previously observed plasticity during the cell fate decision process [22,28,64,65].…”
Section: A Global Pattern Of Nanog and Gata6 Expression In The Icm Stmentioning
confidence: 99%
“…Our results show that the global positional features (see Terminology Box) of NANOG and GATA6 in early blastocysts do not show a pattern. This lack of a pattern might allow for the previously observed plasticity during the cell fate decision process [22,28,64,65].…”
Section: A Global Pattern Of Nanog and Gata6 Expression In The Icm Stmentioning
confidence: 99%
“…The authors propose that lumen expansion is needed for correct lineage segregation ( Ryan et al, 2019 ). Interestingly, in isolated ICMs, epiblast and PE progenitors segregate, although with an increased proportion of PE to epiblast cells ( Wigger et al, 2017 ). This result suggests that, although the second cell fate decision can take place in the absence of the blastocoel, it may be required to fine-tune the relative numbers of epiblast and PE progenitors.…”
Section: The Implanting Embryo: a Global Transformationmentioning
confidence: 99%
“…To identify a simplified system to study this lineage segregation, we first confirmed, as shown in (18), that pEPI and pPrE cells in ICMs isolated from E3.5 or E3.75 blastocysts can segregate and commit to EPI and PrE in culture without trophectoderm (Fig. S2a).…”
Section: R a F Tmentioning
confidence: 78%